Internal auditing and its role in risk management in commercial banks: A field study of the Algerian Popular Credit Bank, Batna Agency - Assma, Boudounet; Amira, Bahri (International journal of economic perspectives, 2024)
This study aimed to identify internal auditing and its role in activating risk management in commercial banks, as it plays an important role in enhancing risk management. To address the research problem, we conducted a survey at the Algerian Popular Credit Bank in Batna province by distributing a questionnaire to employees of Batna Agency. This was done to understand the role of internal auditing in activating risk management in banks. The study reached a set of findings, the most important of which are: the contribution of internal auditing to analyzing and understanding bank risks and how to manage them; risk management requires an effective administration to develop a strategy through which risks faced by banks are diagnosed; there is coordination between the internal audit department and risk management at the Algerian Popular Credit Bank through information exchange, with the aim of reducing the severity of banking risks so that the bank can achieve its objectives of continuity; there is an effective and positive contribution of the internal audit function to the risk management process in the bank.